Mechanisms of Fish Macrophage Antimicrobial Immunity - Grayfer, Leon; Kerimoglu, Baris; Yaparla, Amulya; Hodgkinson, Jordan W.; Xie, Jiasong; Belosevic, Miodrag (Frontiers in Immunology, 2018)
Overcrowding conditions and temperatures shifts regularly manifest in large-scale infections of farmed fish, resulting in economic losses for the global aquaculture industries. Increased understanding of the functional mechanisms of fish antimicrobial host defences is an important step forward in prevention of pathogen-induced morbidity and mortality in aquaculture setting. Similar to other vertebrates, macrophage lineage cells are integral to fish immune responses and for this reason, much of the recent fish immunology research has focused on fish macrophage biology. These studies have revealed notable similarities as well as striking differences in the molecular strategies by which fish and higher vertebrates control their respective macrophage polarization and functionality. In this review, we address the current understanding of the biological mechanisms governing teleost macrophage functional heterogeneity and immunity, focusing on the key cytokine regulators driving fish macrophage development and the control of their antimicrobial armamentarium.